Scalable production of structurally colored composite films by shearing supramolecular composites of polymers and colloids - Li, Miaomiao; Peng, Bolun; Lyu, Quanqian; Chen, Xiaodong; Hu, Zhen; Zhang, Xiujuan; Xiong, Bijin; Zhang, Lianbin; Zhu, Jintao (Nature communications, 2024)
Structurally colored composite films, composed of orderly arranged colloids in polymeric matrix, are emerging flexible optical materials, but their production is bottlenecked by time-consuming procedures and limited material choices. Here, we present a mild approach to producing large-scale structurally colored composite films by shearing supramolecular composites composed of polymers and colloids with supramolecular interactions. Leveraging dynamic connection and dissociation of supramolecular interactions, shearing force stretches the polymer chains and drags colloids to migrate directionally within the polymeric matrix with reduced viscous resistance. We show that meter-scale structurally colored composite films with iridescence color can be produced within several minutes at room temperature. Significantly, the tunability and diversity of supramolecular interactions allow this shearing approach extendable to various commonly-used polymers. This study overcomes the traditional material limitations of manufacturing structurally colored composite films by shearing method and opens an avenue for mildly producing ordered composites with commonly-available materials via supramolecular strategies. Structurally coloured composite films are flexible optical materials with potential in a range of applications, but their production is impacted by long time-frames and limited materials. Here, the authors report a method for the production of large scale films by shearing supramolecular composites.